DAMPAK SOSIAL PABRIK PENGOLAHAN GETAH KARET PT PP LONSUM DI DESA TAMMATTO KECAMATAN UJUNG LOE KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This journal was created to describe how the social impact that occurred on the community since the establishment of the rubber processing plant PT. PP LONSUM in Tammatto Village, Ujung Loe District, Bulukumba Regency and how the social life of the community since the establishment of the rubber processing plant PT. PP LONSUM in Tammatto Village, Ujung Loe District, Bulukumba Regency. In the explanation of this journal, the research is qualitative research that uses descriptive analysis methods where the research methodology is through sociological and phenomenological approaches through various series of activities such as observation, interviews, and documentation. While the data analysis used is data reduction, data presentation, and conclusion withdrawal. The results of this study show that the social life of the community with the company factory PT PP London Sumatra is very helpful to the community around the company to their welfare especially helping to meet their daily needs both clothing, food, and boards. The social impact with the factory company PT PP London Sumatra Ujung Loe District Bulukumba regency is seen from the positive impact can already help the community by opening jobs for the surrounding community. Of course, also in the company certainly has a negative impact, namely the occurrence of environmental pollution, the occurrence of eye shifts, and the loss of people's personalities.